Disaster Risk Assessment, Reduction and Resilience: Their Reciprocal Contribution with Urban Planning to Advance Sustainability. - Bignami, Daniele F. (Springer, 2020)
The chapter illustrates the need for the inclusion in sustainable urban planning of the problem of the impact of disasters on cities and communities: disasters that will continue to occur and may well even become more frequent because of urban expansion, increasing population densities and climate change effects. To achieve this result, first of all some basic tools about disaster terminology, disaster trends and disaster risk computation are provided. Subsequently, the latest international decisions at global level to face disasters and climate change and to promote sustainability are explained and elucidated, showing their connections and synergies. In the final part, some originally selected elements on how to put in place strategies and those actions which are no longer deferrable are proposed.
Keywords: Nachhaltige Stadtentwicklung; Katastrophenschutz; Naturkatastrophe; Risikomanagement; Wetterschaden; Klimawandel; Risikoabschätzung; Risikominderung; Grünplanung